SISTEM PEMERINTAHAN NEGARA REPUBLIK INDONESIA - Rohayuningsih, Heri; Mar’atun, Umi (Faculty of Social Science, Universitas Negeri Semarang, 2011)
Based on the 1945 Constitution, original or ammended, the form ofÃ‚Â Indonesian countyr is a unitary state, while its form of government is republican. Meanwhile, the government system, based on the original 1945 Constitution is not a pure presidential system of government or quasi-presidential system. This is because the AssemblyÃ¢â‚¬â„¢ role is large enough in managing state life. The President is the mandatory of the Assembly, so his position is highly dependent on the votes of the legislative (DPR) and the Assembly (MPR). In the post-reform era, after going through four amendments, Indonesian system is no longer a impure presidential administration, but was moving away as a pure presidential system. This is based on the following indicators. First, the President is no longer be mandatory of the Assembly, so it does not depend on it. Secondly, the position of the Assembly and the President are equally high as the state agency. Third, the president is elected directly by the people, no longer elected by the Assembly. Key words: state structure, form of government, systems of government.